Rethinking the history of plague in the time of COVID‐19. (27th July 2020) - Varlık, Nükhet
Abstract: We are currently experiencing one of the most disruptive pandemics in modern history. The outbreak of COVID‐19 that was first recorded in Wuhan, China and quickly spread across the globe has resulted in nearly 5 million confirmed cases to date and more than 300, 000 deaths. Where we stand now, it is still uncertain how many it will infect or kill worldwide, how long it will continue, and when—if ever—life will return to normal. What we know for sure is that this is a pivotal moment and that we are experiencing a historic event that will transform our societies both profoundly and irreversibly. As we wade into this new age of pandemics, it is critical to rethink how we write the history of pandemics. With a conviction that the past helps us to understand the present and that the present should help us to rethink the past, I turn to the legacy of past plagues. In this essay, I take stock of the lasting legacies of past plagues because they continue to shape the way we think about new pandemics. In particular, I address persistent problems, such as European exceptionalism, triumphalism, and epidemiological Orientalism, that are not only ubiquitous in plague studies, but also staples of public opinion about pandemics, past and present.